Enhancement of Pd Catalytic Activity toward Ethanol Electrooxidation by Atomic Layer Deposition of SnO2 onto TiO2 Nanotubes - Barr, Maissa K. S.; Assaud, Loic; Brazeau, Nicolas; Hanbuecken, Margrit; Ntais, Spyridon; Santinacci, Lionel; Baranova, Elena A. (Journal of Physical Chemistry C, 2017)
Palladium nanoparticles and SnO2 layers have been grown by two successive steps of atomic layer deposition onto TiO2 nanotubes (TNTs). The three-dimensional nanostructured catalytic systems have been studied for ethanol electrooxidation in alkaline media. Characterization by scanning and transmission electron microscopies, X-ray photoelectron spectroscopy, and X-ray diffraction indicates the high conformity, the high purity, and the perfect stoichiometry of Pd and SnO2 deposits onto the TNTs. The electrochemical investigations performed by cyclic voltammetry and chronoamperometry have revealed the beneficial effect of the annealing of the support toward ethanol electrooxidation reaction. The comparison of the catalytic activity with literature shows that such SnO2-based substrates exhibits highly promising performances.
Created from Fastlane, Scopus look-up